Stochastic Perturbation of Optical Solitons for the Concatenation Model with Power-Law of Self-Phase Modulation Having Multiplicative White Noise (Contemporary Mathematics, 2024)
Addressing the concatenation model, this paper explores the incorporation of power-law self-phase modulation and spatio-temporal dispersion, in addition to the chromatic dispersion. The inclusion of the white noise effect, along with deterministic Hamiltonian perturbation terms of arbitrary intensity, is also examined. Two integration approaches are applied to recover the soliton solutions, leading to the observation that the white noise effect remains confined to the phase component of these solutions.
Keywords: solitons, concatenation, power-law, stochastic, perturbations, Kudryashov